Consumo, digestibilidade aparente e balanço de nitrogênio em ovelhas alimentadas com diferentes níveis de fibra em detergente neutro - Macedo Junior, Gilberto de Lima; Sousa, Luciano Fernandes; Godoi, Fernanda Nascimento de; Perez, Juan Ramon Olalquiaga; França, Patricia Maria de [UNESP]; Almeida, Thais Romano Vasconcelos; Paula, Oiti José de; Assis, Roberta de Moura (FapUNIFESP (SciELO), 2012)
This research was carried to investigate the effect of different levels of forage neutral detergent fiber (fNDF) in the diet offered to ewe on the intake and apparent digestibility of the diet and on nitrogen balance. Sixteen adult, non-pregnant and non-lactating Santa Ines ewes, weighting 45.01 ± 5.15 kg, were used. The experimental design used was a 4x4 latin square, with four treatments (8.67%; 17.34%; 26.01% and 34.69% of fNDF) four animals and four periods. The intake of dry matter (DM), organic matter (OM), gross energy (GE), digestible energy (DE), metabolizable energy (ME), crude protein (CP), digestible protein (DP), neutral detergent fiber (NDF) and acid detergent fiber (ADF) were influenced positively by the levels of fNDF of the treatments. The apparent digestibility of DM, OM, GE and ADF wereinfluenced by treatments. Nitrogen balances were positive at all levels of forage NDF. This study made it clear that there is a physiological limit to the use of concentrate in diets offered to ewe, being necessary a minimum amount of forage NDF in the diet to reach the maximum efficiency of nutrients use; however, this limit seems to be inferior at the lowest level of fNDF of the current study.
Voluntary intake, apparent digestibility and nitrogen balance in ewes fed diets with different neutral detergent fiber levels
Keywords: Animal nutrition; Metabolism; Ruminants; Animalia; Bovidae